Eyebrow growth pattern analysis in patients with eyebrow hypotrichosis after receiving topical treatment: A retrospective study. (21st September 2019) - Suchonwanit, Poonkiat; Thammarucha, Sasima
Abstract: Background: Differences in growth patterns among the various parts of the eyebrow have been observed. Aims: We aimed to investigate changes in the hair density and diameter and analyze the eyebrow growth pattern of each eyebrow part (head, body, and tail) in patients with eyebrow hypotrichosis over a 24‐week course of topical treatment. Patients/Methods: A retrospective study of 48 patients who received treatment with bimatoprost 0.01% was conducted. Patient demographic data were collected; measurements of hair density and diameter in the different parts of the eyebrow were collected and statistically evaluated. Results: The tail of the eyebrow revealed the lowest baseline eyebrow density and diameter. Significant changes in eyebrow density ( P  = .01) and diameter ( P  = .01) were first detected in the tail at 4 and 16 weeks of treatment, respectively. The head and body showed a comparable growth pattern. Conclusions: This study confirms the previous observations that hair density, diameter, pattern of growth, and hair growth cycle vary according to their anatomical location within the eyebrow. A better understanding of eyebrow growth pattern could provide the precise pathomechanism of eyebrow hypotrichosis leading to a standardized treatment protocol.